2016
DOI: 10.1021/acs.est.5b04314
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Dissolved Black Carbon Released from Biochar: Reactive Oxygen Species Generation and Phototransformation

Abstract: Dissolved black carbon (BC) released from biochar can be one of the more photoactive components in the dissolved organic matter (DOM) pool. Dissolved BC was mainly composed of aliphatics and aromatics substituted by aromatic C-O and carboxyl/ester/quinone moieties as determined by solid-state nuclear magnetic resonance. It underwent 56% loss of absorbance at 254 nm, almost complete loss of fluorescence, and 30% mineralization during a 169 h simulated sunlight exposure. Photoreactions preferentially targeted ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
193
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(226 citation statements)
references
References 51 publications
13
193
5
Order By: Relevance
“…Due to their unique structure and properties, increasing works have found that the dissolved and nano-biochar possessed Fig. 1 Schematic illustration of the relationship among the structural properties, the reactivity of biochar, functionalization and device of biochar and their environmental applications 1 3 significant different environmental behaviours, including chemical and colloidal stability, mobility in porous media, reactivity and toxicity (Fu et al 2016;Lian and Xing 2017;Liu et al 2018a;Zhang et al 2019). In summary, the difference in biochar size leads to different elemental composition and physicochemical properties between bulk biochar and small-sized biochar.…”
Section: Macroscopic: Bulk Biochar Dissolved and Nano-biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their unique structure and properties, increasing works have found that the dissolved and nano-biochar possessed Fig. 1 Schematic illustration of the relationship among the structural properties, the reactivity of biochar, functionalization and device of biochar and their environmental applications 1 3 significant different environmental behaviours, including chemical and colloidal stability, mobility in porous media, reactivity and toxicity (Fu et al 2016;Lian and Xing 2017;Liu et al 2018a;Zhang et al 2019). In summary, the difference in biochar size leads to different elemental composition and physicochemical properties between bulk biochar and small-sized biochar.…”
Section: Macroscopic: Bulk Biochar Dissolved and Nano-biocharmentioning
confidence: 99%
“…Moreover, the size (nano) effect is also reflected in biochar. For example, photochemistry of dissolved black carbon released from bulk biochar can be more photoactive than that of its matrix (Fu et al 2016). Similarly, biochar was categorized into sedimentary particles, suspended coarse particles and soluble components and ultrafine particles according to their sizes and suspension property.…”
Section: Introductionmentioning
confidence: 99%
“…Sunlight acts to either completely oxidize OC to carbon dioxide (CO 2 ; Cory et al, 2014;Miller & Zepp, 1995) or partially oxidize OC to compounds that accumulate in different ecosystems. A wide range of OC sources in the air, land, and water are susceptible to partial photo-oxidation, including aerosols (Jimenez et al, 2009), plant litter (Austin & Vivanco, 2006), crude oil (Payne & Phillips, 1985;Ward, Sharpless, et al, 2018), pollutants (Boreen et al, 2003), biomolecules (Boreen et al, 2008;Lundeen & McNeill, 2013), black carbon (Fu et al, 2016;Ward et al, 2014), lipids (Collins et al, 2018), and dissolved (DOC;Latch & McNeill, 2006;Cory et al, 2010;Cory et al, 2014) and particulate OC (Estapa & Mayer, 2010). In light of the growing awareness that partial photo-oxidation can be a critical control on the fate and transport of OC, there is a need for robust methods to quantify its occurrence in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the various laboratories using NaBH 4 as a reductant (Leenheer et al 1987;Tinnacher and Honeyman 2007;Ma et al 2010;Sharpless 2012;Phillips and Smith 2014;Fu et al 2016), no standard protocol exists for reducing HS and CDOM, making inter-laboratory comparisons challenging. In one example, NaBH 4 was added in a one-to-one mass ratio to a sample of HS, allowed to reduce for 4 h, with the excess NaBH 4 then decomposed by the addition of hydrochloric acid before subsequent isolation by solid phase extraction (Leenheer et al 1987).…”
mentioning
confidence: 99%